PEREMPUAN SEBAGAI KORBAN KEKERASAN SEKSUAL: APAKAH HUKUM SUDAH CUKUP MEMBERIKAN KEADILAN? - Faisal, Faisal; Ghazali, Mardania; Umar, Mahmud Hi.; Djafar, Muhammad Mufti M. (UI Scholars Hub, 2023)
Sexual violence is not a new thing heard in the ears of the Indonesian people. Sexual violence is a serious form of crime that should be a serious concern for the government. The Commission on Violence Against Women notes that every two hours, there are 3 Indonesian women who experience sexual violence. This is what makes Indonesia in a state of emergency sexual violence. In fact, sexual violence is still common in Indonesia. The number of victim blaming that occurs in the community, tends to blame victims of sexual violence. Even though the facts show that the impact of sexual violence on victims is very serious and traumatic and can last a lifetime. The presence of a new Criminal Code and also a special law discussing sexual violence is expected to minimize cases of sexual violence that occur.